GROWTH AND FATTY ACID COMPOSITION OF MARINE MICROALGA NANNOCHLOROPSIS sp IN MEDIUM ENRICHED WITH MAGNESIUM - J. Tri astuti; Lies Sriwuryandari; Ekoputro Agung Putro; T. Sembiring (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Micro-algae are to be an attractive way to produce bio-diesel due to high photosynthetic yields and lipid accumulation in cells. This high productivity combined with possibility to uptake CO2 stimulated its utilization as a biological mitigation method of CO2, at once as an alternative renewable source of energy. Growth characteristics and chemical composition of micro-algae can be altered by culture environment. Nutrient sufficiency,included magnesium element (Mg2+) is important factors on overall biochemical composition. In study, Nannochloropsis sp was cultivated in Erlenmeyer 250 ml containing 200 ml f/2 medium. There are three groups of treatment with different levelof magnesium (Mg2+), i.e. 0 (M0); 0.1mgL-1 (M1); and 1.0 mgL-1 (M2). All treatment was designed triplicate in batch system. Culture was then aerated continuously with sterile atmospheric air (1.5 L.min-1). Cells were harvested on 25th day after inoculation and analyzed. Data showed that Chlorophyll-a increased linearly with time and maximum at 18th days of growth period, i.e. 23.57; 26.44; and 27.74mgL-1, for M0; M1; and M2,respectively. Chlorophyll-a content decreased significantly when pH dropped to 5-6.Enrichment with Mg2+ increased the chlorophyll-a content 12.2-17.7%. Dry cell reached 375-400mgL-1 in all treatment. Lipid content of Nannochloropsis sp in control (M0) is 55.3%, higher than M1 and M2. Saturated fatty acid tends to increase from 80.70 (M0)to 96.70 (M1) and 94.53% (M2). Fatty acid of M0 and M1 was composed dominantly by palmitic acid (C16:0), i.e. 49.19-70.75% total fatty acids. Meanwhile, M2 treatment was dominantly by lauric acid (C12:0), i.e. 32.98%.Keywords: CO2 biological mitigation, chlorophyll-a, fatty acid, lipid, agnesium,microalgae, Nannochloropsis sp, photosynthesis.